2019
DOI: 10.1007/s00467-019-04371-y
|View full text |Cite
|
Sign up to set email alerts
|

Bartter and Gitelman syndromes: Questions of class

Abstract: Bartter and Gitelman syndromes are rare inherited tubulopathies characterized by hypokalaemic, hypochloraemic metabolic alkalosis. They are caused by mutations in at least 7 genes involved in the reabsorption of sodium in the thick ascending limb (TAL) of the loop of Henle and/or the distal convoluted tubule (DCT). Different subtypes can be distinguished and various classifications have been proposed based on clinical symptoms and/or the underlying genetic cause. Yet, the clinical phenotype can show remarkable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 55 publications
1
45
0
2
Order By: Relevance
“…Lo anterior fue compatible con el síndrome de Gitelman, patología en la cual existe una alteración de la reabsorción de sodio en el túbulo contorneado distal, por mutación del cotransportador sodio-cloro, lo que conlleva al desarrollo de hiperaldosteronismo secundario. (13). En este síndrome los pacientes por lo general debutan durante la adolescencia con alcalosis metabólica hipocaliémica con presión arterial normal, a pesar del hiperaldosteronismo, como fue el caso del paciente en mención; asociado a esto, los pacientes típicamente cursan con hipocalciuria e hipomagnesemia, en contraste con el síndrome de Bartter donde la hipercalciuria es la característica distintiva (14).…”
Section: Discussionunclassified
“…Lo anterior fue compatible con el síndrome de Gitelman, patología en la cual existe una alteración de la reabsorción de sodio en el túbulo contorneado distal, por mutación del cotransportador sodio-cloro, lo que conlleva al desarrollo de hiperaldosteronismo secundario. (13). En este síndrome los pacientes por lo general debutan durante la adolescencia con alcalosis metabólica hipocaliémica con presión arterial normal, a pesar del hiperaldosteronismo, como fue el caso del paciente en mención; asociado a esto, los pacientes típicamente cursan con hipocalciuria e hipomagnesemia, en contraste con el síndrome de Bartter donde la hipercalciuria es la característica distintiva (14).…”
Section: Discussionunclassified
“…There is still much to learn about proteins that are involved in the expression and activity of the mutated transporters. Since there is still a subgroup of patients in whom no mutation can be found in the genes that are currently known to cause SLT, a deeper investigation of uEV proteome in these syndromes could lead to the discovery of dysregulated species and it could possibly generate targets for future treatments [2,6].…”
Section: Discussionmentioning
confidence: 99%
“…Gitelman syndrome (GS) and Bartter syndrome (BS) are rare inherited salt-losing tubulopathies (SLT) characterized by hypokalaemic, hypochloraemic metabolic alkalosis [1,2]. They are marked by lower sodium chloride reabsorption of the distal nephron, which results in extracellular volume contraction and increased activity of the renin angiotensin aldosterone system [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a recently released news report of a fatal case of COVID-19 in a 3-month-old infant with Bartter's syndrome has indicated that ACE2 does have a significant role in COVID-19. This is an interesting example of how rare genetic disorders may contribute to understanding the pathophysiology of common diseases: patients affected with this autosomal recessive tubulopathy have increased ACE2 levels and elevated renin and aldosterone levels (30). However, how these factors actually interact in the case of a SARS-CoV-2 infection remains to be determined.…”
mentioning
confidence: 99%